Ultrafast Sonochemistry-Based Approach to Coat tio2 Commercial Particles for Sunscreen Formulation - Casagrande-Denardin, J; Melo-Freire, R (Elsevier B.V., 2018)
TiO2 is a common inorganic filter used in sunscreens due to its photoprotective effect on the skin against UV radiation. However, the use of this kind of material in cosmetics is limited by its inherent photocatalytic activity. It is known that coating on TiO2 surface can improve some features. Although, many of the methodologies used for this purpose are still laborious and time-consuming. Thus, this work reports a novel, easy, cheap and fast strategy to coat TiO2 particles by using a sonochemistry approach, aiming to decrease photocatalytic activity and to enhance colloidal stability. For this proposal, SiO2, Al2O3, ZrO2 and sodium polyacrylate (PAANa) were used to tune the surface of commercial TiO2 particles and they were applied in a sunscreen formulation. The samples were characterized by XRPD, FT-IR, DLS, EDS, SEM and TEM. The photocatalytic activity and UV-shielding ability were also evaluated. The sunscreen formulations were prepared and characterized by zeta potential, DLS, and Sun Protection Factor (SPF). FT-IR, EDS, and charge surface of the particles confirmed the success of the sonochemistry coating. Additionally, TiO2@Al2O3, TiO2@SiO2 and TiO2@PAANa show a lower photocatalytic activity than original TiO2 with similar UV-shielding ability. The sunscreens produced with the coated TiO2 have similar SPF to the one with commercial TiO2. Specifically, the sunscreen with TiO2@PAANa shows an increase in colloidal stability. Herein, the incorporation of the sonochemical-coated TiO2 particles in sunscreen formulations may produce sunscreens with better aesthetic appearance and a greater health security due to its lower free radicals production. © 2018 Elsevier B.V.